2011
DOI: 10.1021/cm200557e
|View full text |Cite
|
Sign up to set email alerts
|

Thioether Side Chains Improve the Stability, Fluorescence, and Metal Uptake of a Metal–Organic Framework

Abstract: This work builds on the recently developed hardÀsoft approach, as is embodied in the carboxylÀthioether combination, for functionalizing metalÀorganic frameworks (MOFs), and it aims to further demonstrate its efficacy and generality in connection with the prototypic MOF-5 system [i.e., Zn 4 O(bdc) 3 , where bdc is 1,4-benzene dicarboxylate]. Specifically, the thioether side chain CH 3 SCH 2 CH 2 SÀ (methylthioethylenethio, or MSES) is placed at the 2,5-positions of bdc, and the resultant molecule (L) was cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(88 citation statements)
references
References 78 publications
1
87
0
Order By: Relevance
“…ICP and SEM/EDX analyses, combined with single crystal Xray diffraction, confirmed that compound 1 is capable to capture HgCl 2 from aqueous solution as other MOFs [38][39][40][41][42][43][44]57 and COFs, 33,58,59 through the abovementioned dual step capture process to give 0.5HgCl 2 @1 and HgCl 2 @1. The HgCl 2 loading, even in the case of HgCl 2 @1 (ca.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 80%
See 1 more Smart Citation
“…ICP and SEM/EDX analyses, combined with single crystal Xray diffraction, confirmed that compound 1 is capable to capture HgCl 2 from aqueous solution as other MOFs [38][39][40][41][42][43][44]57 and COFs, 33,58,59 through the abovementioned dual step capture process to give 0.5HgCl 2 @1 and HgCl 2 @1. The HgCl 2 loading, even in the case of HgCl 2 @1 (ca.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 80%
“…S11). ] in contaminated aqueous solutions and the time required to achieve such decrease for 1 (red), and different materials reported such as MOFs [38][39][40][41][42][43][44] (green), COFs 33,58,59 (covalent-organic frameworks, blue), POPs 31,32,61 (porous organic polymers, orange), mesoporous silicas 62 (purple) and chalcogels 63 (cyan). Dashed line represent the frontier between contaminated and accepted limits for drinking water.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…8). This represents an advantage of PAF-1-SH for mercury removal across a wide range of pH, particularly when compared with silica and MOFs based adsorbents [12][13][14][15][16][29][30][31][32][33][34] , which usually suffer from the loss of porosity under such harsh conditions. Mercury adsorption experiments under acid and basic conditions revealed that PAF-1-SH also exhibits high affinities for Hg(II) with K d values of 6.66 Â 10 7 ml g À 1 at pH 1.0 and 2.49 Â 10 7 ml g À 1 at pH 12.8, which render excellent capability of reducing Hg(II) concentrations from 10 p.p.m.…”
Section: Synthesismentioning
confidence: 99%
“…Thiol/thio-functionalized adsorbents, including clays 10 , resins 11 , mesoporous silica [12][13][14][15][16] , activated carbons 17 , mesorporous carbons 18 and chalcogenides 19,20 , are considered very effective sorbents for Hg(II) removal from aqueous solutions due to the soft-soft interaction 21 . Recently, metal-organic frameworks (MOFs) [22][23][24][25][26][27][28] have been explored as a new type of adsorbents for mercury removal [29][30][31][32][33][34] due to their high surface areas, but they usually suffer from instability in water 29,30 or aqueous solutions with a wide pH range 34 and possess low adsorption capacity and weak affinity for Hg(II).…”
mentioning
confidence: 99%
“…They are promising as light emitting materials with a wide range of colors provided by inorganic metal centers, organic linkers, guest solvent molecules, as well as metal-organic charge transfer [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. In addition, the emitted color can also be readily modulated by different lanthanide ions and their concentrations, guest species, and excitation wavelengths [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%